Mineralization dynamics of metakaolin-based alkali-activated cements. (April 2017) - Gevaudan, Juan Pablo; Campbell, Kate M.; Kane, Tyler J.; Shoemaker, Richard K.; Srubar, Wil V.
Abstract: This paper investigates the early-age dynamics of mineral formation in metakaolin-based alkali-activated cements. The effects of silica availability and alkali content on mineral formation were investigated via X-ray diffraction and solid-state 29 Si magic-angle spinning nuclear magnetic resonance spectroscopy at 2, 7, 14, and 28 days. Silica availability was controlled by using either liquid- (immediate) or solid-based (gradual) sodium silicate supplements. Mineral (zeolitic) and amorphous microstructural characteristics were correlated with observed changes in bulk physical properties, namely shrinkage, density, and porosity. Results demonstrate that, while alkali content controls the mineralization in immediately available silica systems, alkali content controls the silica availability in gradually available silica systems. Immediate silica availability generally leads to a more favorable mineral formation as demonstrated by correlated improvements in bulk physical properties.